Knowledge and practices of food service staff regarding food safety and food hygiene in the Capricorn District Hospitals in the Limpopo Province, South Africa - Mashuba, Dorcus Mmaphefo (My University, 2016)
The purpose of this study was to assess the knowledge and practices of food service staff regarding food safety and food hygiene in Capricorn District hospitals, Limpopo Province. Quantitative, cross-sectional research was conducted to determine the knowledge and practices of food service staff. A convenient sampling technique was employed to select 84 food service staff members (11 food service supervisor and 73 food service aids). Data collection was done using structured questionnaires. Food service staff members consisting of food service aids and food service supervisors participated in the study. The data were analysed using the statistical package for social sciences version 23. Of the respondents 50 (60%) are female whereas 34 (40%) are males. The largest group of them, 34 (40%) had secondary education, 23 (27%) had matric whereas 16 (19%) had post matric qualifications. 80 (95%) of them answered correctly that they use an air dryer or paper towel for drying hands after washing whereas 65 (77%) answered incorrectly when asked the difference between washing and sanitizing. Seventy eight of the respondents answered correctly on practice questionnaire that they only reheat leftovers once whereas 69 (82%) answered incorrectly about the temperature one should maintain for potentially hazardous food that has been cooked and needs to be reheated. In this study a significant correlation was observed between level of education and knowledge, with p-value 0.016 and again between level of education and practices (p-value 0.024), also between work activity and practice (p-value 0.021). There was significant difference between knowledge level and practice with p-value 0.045. The result of the study suggest that although most food service staff are knowledgeable regarding some aspects of food hygiene and food safety significant gaps remains in food safety practices, posing risk to hospitalised patients who are already vulnerable. There is a need for training in areas were food service staff are lacking knowledge.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: Food service; Food safety; Food hygiene; Food -- Safety measures; Food service -- Safety measures; Food handling -- Safety measures; Food poisoning